Ideological congruence and socio-economic inequality. Issue 3 (1st March 2018) - Schakel, Wouter; Hakhverdian, Armen
Abstract : This study examines whether or not political representation in the Netherlands is biased toward the rich and higher educated by comparing the political orientations of members of parliament to those of the electorate. The analyses reveal stark differences in the representation of different socio-economic groups. The political views of elected national representatives are far more similar to those of rich, higher educated citizens than to those with less income and education. Moreover, a longitudinal analysis reveals that inequalities in political representation have actually grown in recent years. We also show that the use of measures of ideological self-identification might to lead to highly misleading results regarding the nature of political representation as opposed to the use of issue items. We conclude that, despite a highly proportional electoral system, the views which are represented in the Dutch lower house of parliament contain major distortions of the views of the broader electorate.